2020
DOI: 10.1002/elps.202000010
|View full text |Cite
|
Sign up to set email alerts
|

Separation of terbutaline enantiomers in capillary electrophoresis with neutral cyclodextrin‐type chiral selectors and investigation of the structure of selector‐selectand complexes using nuclear magnetic resonance spectroscopy

Abstract: The major goal of this study was to determine the affinity pattern of the terbutaline (TB) enantiomers toward α‐, β‐, γ‐, and heptakis(2,3‐di‐O‐acetyl)‐β‐cyclodextrins and using NMR spectroscopy for the understanding of the fine mechanisms of interaction between the cyclodextrins (CD) and TB enantiomers. It was shown once again that CE in combination with NMR spectroscopy represents a sensitive tool to study the affinity patterns and structure of CD complexes with chiral guests. Opposite affinity patterns of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…The authors concluded that it may be difficult to draw conclusions on the complex structures by NMR in some cases. Even the simultaneous presence of both complexes (1) and (2) in solution could not be ruled out [77]. Interestingly, formation of a complex between TER and 2,3-DM-β-CD could not be derived by NMR spectroscopy explaining the lack of resolution observed in CE experiments, while TER formed an inclusion complex with 2,6-DM-β-CD (Figure 1) [79].…”
Section: Structures Of Selector-selectand Complexesmentioning
confidence: 98%
See 3 more Smart Citations
“…The authors concluded that it may be difficult to draw conclusions on the complex structures by NMR in some cases. Even the simultaneous presence of both complexes (1) and (2) in solution could not be ruled out [77]. Interestingly, formation of a complex between TER and 2,3-DM-β-CD could not be derived by NMR spectroscopy explaining the lack of resolution observed in CE experiments, while TER formed an inclusion complex with 2,6-DM-β-CD (Figure 1) [79].…”
Section: Structures Of Selector-selectand Complexesmentioning
confidence: 98%
“…Interestingly, application of α‐CD and HMDS‐β‐CD, which resulted in the migration order S > R, did not result in the formation of inclusion complexes. Instead, external complexes were concluded from ROESY data indicating spatial proximity of the phenyl ring to the secondary wider rim of α‐CD [77]. In case of HMDS‐β‐CD, nuclear Overhauser effects (NOEs) were observed between the methyl protons of the TER tert ‐butyl moiety and a methylene group of the side chain [76].…”
Section: Fundamental Aspects Of Ce Enantioseparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of different substituents alters the enantioselectivity of the modified β-CDs. Modified β-CDs can be created in neutral [141,143], cationic [144][145][146] and anionic forms [147,148]. Cyclodextrin (CD) and its derivatives are among the most preferred chiral selectors in CE due to their chemical resistance, conveniences related to their structural properties and low UV absorptions [149][150][151].…”
Section: Cyclodextrins and Its Derivatives As Chiral Selectorsmentioning
confidence: 99%